Study Of Echo Feature In Imam Mosque In Isfahan And Its Function In New Buildings Like Amphitheater - Khoeini, Reza; Torabi, Zohreh (The Turkish Online Journal of Design Art and Communication, 2016)
The aim of this project is to acoustically investigate Imam Mosque in Isfahan. If anyone ever has seen Imam Mosque, one of the things that have to try is the reflection of sound in this mosque. There is an interesting feature alongside the beautiful architecture that could attract every tourist. The purpose of this design was not only to attract tourists. This is an excellent engineering that has been done purposefully. In the past, due to the lack of advanced audio technology, there were problems to voice one speaker to the audience. In the same period Sheikh Baha'i designed the dome of Imam Mosque to sound even when the speaker does not speak so easily reach to the whole audience. Accordingly, research with descriptive approach and the library methods of data collection (by reviewing historical documents and primary sources) tries to introduce the new perspective of the architectural features of the mosque in the area of innovative design in the architecture community. As a result, this research examined the dome to use technology in the design of today's conference halls.
Keywords: Echo; acoustic; sound reflection; amplification; Yankı; akustik; ses yansıması; amplifikasyon